ACADEMIC PROGRAMME OBJECTIVES AND LEARNING OUTCOMES - Alexandr I. Chuchalin (Высшее образование в России)
The paper considers approaches to assessment of engineering programme objectives and learning outcomes achievement for accreditation. Accreditation criteria of the Accreditation Board for Engineering and Technologies (USA) and the Association for Engineering Education of Russia are discussed. The bachelor degree programme in Power and Electrical Engineering at Tomsk Polytechnic University is used as an example. The approaches are recommended for implementation in Russian University Academic Standards and a new version of the Federal State Education Standards.